2001
DOI: 10.1007/s004420000503
|View full text |Cite
|
Sign up to set email alerts
|

Dwarf mistletoe affects whole-tree water relations of Douglas fir and western larch primarily through changes in leaf to sapwood ratios

Abstract: Dwarf mistletoes induce abnormal growth patterns and extreme changes in the biomass allocation of their hosts as well as directly parasitizing them for resources. Because biomass allocation can affect the resource use and efficiency of conifers, we studied the influences of dwarf mistletoe infection on above-ground biomass allocation of Douglas fir and western larch, and the consequences of such changes on whole-tree water use and water relations. Sap flow, tree water potentials, leaf:sapwood area ratios (A :A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 43 publications
4
73
0
Order By: Relevance
“…Sala et al (2001) found that foliage in infected Douglas-fir branches have lower water-use efficiency, but infected trees do not have higher water use overall. Their results indicate that infected trees compensate for lower water-use efficiency by increasing sap flow during times of moderate water availability.…”
Section: Mean Sensitivitymentioning
confidence: 94%
See 2 more Smart Citations
“…Sala et al (2001) found that foliage in infected Douglas-fir branches have lower water-use efficiency, but infected trees do not have higher water use overall. Their results indicate that infected trees compensate for lower water-use efficiency by increasing sap flow during times of moderate water availability.…”
Section: Mean Sensitivitymentioning
confidence: 94%
“…Additional evidence indicates that infection increases needle surface area while decreasing volume (Tinnin and Knutson 1980;Wanner and Tinnin 1986). Such shifts in the distribution of biomass in the host crown could lower water-use efficiency, resulting in lower tolerance to drought stress (Sala et al 2001). Sala et al (2001) also reported that foliage in infected branches has lower water-use efficiency when compared to uninfected branches in Douglas-fir (Pseudotsuga menziesii Mirb.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4b). This may be partially ascribed to the higher osmotic potential of the mistletoe foliage (Sala et al 2001) and to the higher water capacitance of the "succulent-like" Loranthus leaves (Glatzel 1983). In the second hypothesis (transpiration from the succulentlike leaves without the propagation of pressure to the xylem), rehydration of the leaf tissues would have to occur at the expense of evening transpiration (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to photosynthate reallocation, holoparasitic plants may stimulate the secretion of hormones by the host plant, directly inoculating the host structures with their own hormones or mRNA (Knutson 1979;Ihl et al 1984;Westwood et al 2010). In this sense, holoparasitic plants may negatively impact many metabolic and physiological aspects of their host plants, such as stomata opening, photosynthesis rate, transpiration, hormone secretion or water-use efficiency (Goldstein et al 1989;Fernandes et al 1998;Sala et al 2001;Runyon et al 2008;Prider et al 2009). …”
mentioning
confidence: 99%